Prescriptive Theorizing in Management Research: A New Impetus for Addressing Grand Challenges - Hanisch, Marvin (Journal of Management Studies, 2024)
AbstractAlthough management research has a rich tradition of both descriptive and prescriptive theorizing, the latter is often (and erroneously) viewed as unscientific, purely practice‐oriented, or simply a corollary of descriptive analysis. Prescriptive theorizing concerns how things should be and how they can be achieved, as opposed to descriptive theorizing, which focuses on why or how things are (interrelated). Accordingly, prescriptive theorizing has strong normative and instrumental properties, which are especially relevant when addressing pressing societal, ecological, and ethical concerns, also referred to as grand challenges, that demand a re‐evaluation of established norms and behavioural patterns. However, this opportunity is currently underutilized in the management literature, and there is a lack of guidance on how to leverage the principles of prescriptive theorizing. Therefore, I clarify its main characteristics, outline how scholars can construct rigorous prescriptive arguments, and show how normative and instrumental reasoning can promote positive social change. Embracing prescriptive theorizing as a vital complement to descriptive theorizing in management research provides scholars with an intellectual toolkit to actively engage in the urgent discourse on grand challenges and develop compelling new and impactful theories.